Cell free supernatant for sustainable crop production - Alori, Elizabeth Temitope; Onaolapo, Abidemi Olubusayo; Ibaba, Ayibanoa Lekoo (Frontiers in Sustainable Food Systems, 2025)
The increase in demand for food production due to the ever-increasing human population across the world requires that food production should grow exponentially. For agricultural food production to meet the needs of human requirements and demands there is a need for sustainable practices that will ensure production and availability of food without affecting soil health, soil biota and soil fertility. Over the years, many plant growth promoting bacteria (PGPB) strains have been identified and reported to provide a number of benefits to plants, including enhanced nutrient uptake, growth, and development as well as increased resistance to biotic and abiotic stress. However only a small number of them, are sold today, mostly due to the formulations’ inability to support bacterial survival both during and after application in agroecosystems. PGPB strains that present these difficult constraints can be employed in the production of cell-free supernatants (CFSs), which are broth cultures that have undergone various mechanical and physical procedures to eliminate cells. The available literature suggests that CFS may be a reliable source of secondary metabolites for sustainable agriculture. This review therefore discusses cell free supernatant of various soil microorganisms that have been used in crop production and offered pertinent information about CFS for upcoming studies on CFSs as bio stimulant and biocontrol agents in sustainable agriculture. The significance, sources, applications, mechanisms of action of CFS and benefits of studies on CFS agricultural applications—both as a bio fertilizer and a biocontrol agent were studied.